Fast real-time monitoring of entacapone crystallization and characterization of polymorphs via Raman spectroscopy, statistics and SWAXS - Jednačak Tomislav; Hodzic Aden; Scheibelhofer Otto; Marijan Marijan; Khinast Johannes G.; Novak Predrag (Acta Pharmaceutica)
Crystallization of the drug entacapone from binary solvent mixtures was monitored in situ using a Raman optical probe. The recorded Raman spectra and statistical analysis, which included the principal components method and indirect hard modeling made it possible to estimate the starting point of crystallization, to assess crystallization temperatures and to provide information on the polymorphic content of the mixture. It was established that crystallization temperatures were proportional to the volume content of the solvent in mixtures. The samples were also evaluated off-line via Raman spectroscopy and SWAXS. The collected data showed the presence of forms b and g in all solvent mixtures. In a toluene/methanol 30:70 mixture, in addition to forms b and g, at least one of the forms A, D or a was also indicated by SWAXS. The results have shown that the presence of a particular polymorph is strongly dependent on the nature and portion of the solvent in the binary solvent mixture.